PENGARUH PERMAINAN GOBAK SODOR TERHADAP HASIL BELAJAR MATERI KEBUGARAN JASMANI PADA PESERTA DIDIK KELAS 5 SD NEGERI 7 SELAT PENUGUAN - Bima Dwi Pratama; Endie Riyoko; Ilham Arvan Junaidi (STKIP Melawi, 2026)
Abstract: This experimental study (one-group pretest-posttest design) aimed to determine the effect of the gobak sodor traditional game on the physical fitness learning outcomes (40-meter sprint) of 5th-grade students at SDN 7 Selat Penuguan. The primary issue addressed was the students' low running ability. Total sampling was applied, involving the entire population of 21 students. Data were collected through a 40-meter run test and subsequently analyzed using a paired sample t-test. The results showed an increase in the mean score from the pretest (7.83 seconds) to the posttest (6.50 seconds). Hypothesis testing revealed that t count (11.528) > t table (1.725) at a significance level of 0.05, thereby accepting Ha. In conclusion, the gobak sodor game has a significant effect on improving students' physical fitness through running activities and swift movements. Keywords: Gobak Sodor Game, Physical Fitness, Learning Outcomes. Abstrak: Penelitian eksperimen (one-group pretest-posttest) ini bertujuan mengetahui pengaruh permainan gobak sodor terhadap hasil belajar kebugaran jasmani (lari cepat 40 meter) siswa kelas 5 SDN 7 Selat Penuguan. Masalah utama adalah rendahnya kemampuan lari siswa. Sampel jenuh digunakan melibatkan seluruh populasi sebanyak 21 peserta didik. Data dikumpulkan melalui tes lari 40 meter, lalu dianalisis menggunakan paired sample t-test. Hasil menunjukkan peningkatan rata-rata dari pretest (7,83 detik) ke posttest (6,50 detik). Uji hipotesis memperoleh t-hitung (11,528) > t-table (1,725) pada signifikansi 0,05, sehingga Ha diterima. Kesimpulannya, permainan gobak sodor berpengaruh signifikan meningkatkan kebugaran jasmani siswa melalui aktivitas berlari dan gerakan cepat. Kata Kunci: Permainan Gobak Sodor, Kebugaran Jasmani, Hasil Belajar